129k views
4 votes
Please help I dont get how to do it 1/6d+2/3=1/4(d-2)

1 Answer

7 votes

the equation is:


(1)/(6)d+(2)/(3)=(1)/(4)(d-2)

we solve


(1)/(6)d+(2)/(3)=(1)/(4)d-(2)/(4)

simplifying 2/4


(1)/(6)d+(2)/(3)=(1)/(4)d-(1)/(2)

grouping similar terms


(1)/(6)d-(1)/(4)d=-(1)/(2)-(2)/(3)

we solve


-(1)/(12)d=-(7)/(6)
\begin{gathered} d=-(7)/(6)*(-12) \\ d=14 \end{gathered}

User YetAnotherBot
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.